Study on Achieving Harmonious Colour Relationship in Art/Design: Towards a Mathematical Model - Ebigbagha, Zifegha Sylvester (New Horizons in Education and Social Studies Vol. 8, 2021)
Achieving harmonious colour relationship for visual expression is of prime importance in art and design. Mixing pigment colours is often unwieldy, ambiguous, confusing and problematic. Therefore, as a panacea, this paper proposes a mathematical model that would serve heuristic, descriptive, diagnostic, prescriptive, and predictive functions. It used a triangulation of the Critical-Historical-Analytical Examination, Artistic Exploration and Content Analysis methods. The paper started with the need for model to satisfactorily resolve problems associated with mixing colours in harmony. Furthermore, the fundamental features of colour were highlighted. Moreover, it discussed the adoption and adaptation of the Colour Wheel into a set of alphanumeric codes and mathematical proposition (nH I5 + V10 = 1, where n, is the alphabetic representation of a type of harmonious colour scheme; H, is hue; I5 is the intensity scale of five gradation, and V10 is the value scale of ten gradation of the hue selected), for achieving harmonious colour relationship. The alphanumeric codes: M(1), A(1,2,3), DC(1,7), SC(1,6,8), NC(1,6 or 8), TR(1,5,9), B(1,6,10) and TD(1,3,7,9 or 1,4,7,10) represent Monochromatic, Analogous, Direct Complementary, Split Complementary, Near Complementary, Triadic, Balance, and Tetrad schemes respectively. Any hue first selected on the colour wheel is 1, then count clockwise/anticlockwise to choose other number of hues prescribed for a desired scheme. And the paper ended with suggestions that artists and designers should internalize and employ these codes and formula, which with practice, become intuitive and useful.